Wages differentials between the skilled and the unskilled in Singapore. - Ho, Lily. (2008)
This final year project report studies the real determinants that is causing the widening wages gap between the skilled and the unskilled in Singapore. Econometrics regression was used and found that increasing level of education and technology had caused the disparity.